Ethyl 4- (3,5-di-tert-butyl-2-hydroxybenzylidene)amino benzoate - Ariffin, Azhar; Ng, S.W.; Shakir, R.M. (International Union of Crystallography, 2010)
The title compound, a Schiff base, C24H31NO3, has a substituted aromatic ring at both ends of the azomethine linkage and these make a dihedral angle of 24.9 (1)degrees. There is an intramolecular hydrogen bond between the hydroxy group (donor) and the N atom of themazomethine linkage.